1978
DOI: 10.1111/j.1365-2125.1978.tb01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug metabolism in epileptics: in vivo and in vitro correlations.

Abstract: I The effect of inducing drug therapy on the relationship between in vitro (cytochrome P-450 content) and in vivo (antipyrine kinetics) was investigated by comparing eleven consecutively treated epileptics with two groups of controls, eleven subjects with normal liver histology and eleven disease matched non-epileptics, all underwent diagnostic liver biopsy. 2 The epileptics had significantly higher cytochrome P-450 level in biopsies and they also metabolized antipyrine taster than the controls. 3 Decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…This finding was somewhat surprising in the light of the apparent induction of cytochrome P-450 in the present study and of the fact that we and others have previously demonstrated the induction of several monooxygenases and cytochrome P-450 in human liver biopsy samples by inducing drugs (e.g. Schoene et al, 1972;Sotaniemi et al, 1978b). Furthermore, the enzyme is inducible by phenobarbitone in mouse liver microsomes (Wood & Conney, 1974 flavone, SKF-525A, metyrapone, aniline and testosterone.…”
Section: /[S]contrasting
confidence: 70%
“…This finding was somewhat surprising in the light of the apparent induction of cytochrome P-450 in the present study and of the fact that we and others have previously demonstrated the induction of several monooxygenases and cytochrome P-450 in human liver biopsy samples by inducing drugs (e.g. Schoene et al, 1972;Sotaniemi et al, 1978b). Furthermore, the enzyme is inducible by phenobarbitone in mouse liver microsomes (Wood & Conney, 1974 flavone, SKF-525A, metyrapone, aniline and testosterone.…”
Section: /[S]contrasting
confidence: 70%
“…Phenytoin, carbamazepine, phenobarbitone and primidone, when administered in therapeutic doses to patients with epilepsy, are potent inducers of hepatic drug-metabolising enzymes (Perucca and Richens, 1981;Perucca et al, 1979;Sotaniemi et al, 1978). A number of clinically important drug interactions are considered to be mediated by this effect.…”
Section: Drugs Whose Metabolism May Be Stimulated By Anticonvulsantsmentioning
confidence: 98%
“…Our previous investigations have shown a clear correlation between the capacity of the hepatic drug oxidizing enzyme system in vitro, measured by cytochrome P-450, and drug metabolism in vivo Sotaniemi et al, 1977;Sotaniemi, Pelkonen, Ahokas, Pirttiaho & Ahlqvist, 1977;Pirttiaho, Sotaniemi, Ahokas & Pitkiinen, 1978;Pirttiaho, Sotaniemi, Pelkonen & Pitkiinen, 1978). This was also true in the present study, cytochrome P-450 concentration correlating with propranolol plasma clearance.…”
Section: Discussionmentioning
confidence: 99%